Evaluation of pelvic floor muscle anatomy and function in women: modern techniques - Adamiak-Godlewska, Aneta; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2012)
This is a review of studies on modern techniques used to assess the anatomy and function of women’s pelvic floor muscles. The usefulness of different methods of ultrasound examination is explained. The validity and reliability of perineometry, electromyography and hopes connected with dynamometry were also analyzed. According to evidence-based medicine, currently the ultrasound is the most widely used and best method for proper diagnosing and targeted therapy of women’s pelvic floor muscles.